2012
DOI: 10.1186/1472-6882-12-217
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the in vitro cytotoxic, antioxidant, lipase inhibitory and antimicrobial activities of selected Thai medicinal plants

Abstract: BackgroundTraditional folk medicinal plants have recently become popular and are widely used for primary health care. Since Thailand has a great diversity of indigenous (medicinal) plant species, this research investigated 52 traditionally used species of Thai medicinal plants for their in vitro cytotoxic, antioxidant, lipase inhibitory and antimicrobial activities.MethodsThe 55 dried samples, derived from the medicinally used parts of the 52 plant species were sequentially extracted by hexane, dichloromethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 27 publications
0
47
0
3
Order By: Relevance
“…Some other medicinal plants of Thailand such as Bauhinia strychnifolia (vines) and previously mentioned C. fenestratum (stems) were also found to possess in vitro cytotoxic activity in KB3-1 (Kaewpiboon et al, 2012). The highest cytotoxic activity for vines of B. Strychnifolia (IC 50 value of 1.86 μg/ml) was obtained in the DCM extract.…”
Section: Dichloromethane Extractsmentioning
confidence: 75%
See 3 more Smart Citations
“…Some other medicinal plants of Thailand such as Bauhinia strychnifolia (vines) and previously mentioned C. fenestratum (stems) were also found to possess in vitro cytotoxic activity in KB3-1 (Kaewpiboon et al, 2012). The highest cytotoxic activity for vines of B. Strychnifolia (IC 50 value of 1.86 μg/ml) was obtained in the DCM extract.…”
Section: Dichloromethane Extractsmentioning
confidence: 75%
“…Even this compound exhibited strong inhibition of cell proliferation, indicating its effectiveness as another anti-cancer lead compounds from the same plant (Teh et al, 2012). In another study, the crude hexane extract of the vines of B. Strychnifolia have also been found to be highly cytotoxic (IC 50 value of 1.86 μg/ml) in KB3-1 (Kaewpiboon et al, 2012).…”
Section: Hexane Extractsmentioning
confidence: 95%
See 2 more Smart Citations
“…The leaves or a stem in boiling water has been used as a tonic. It has been reported that aqueous leaf extract of B. strychnifolia presented potent antioxidant, anti-inflammation, anti-microbial activities [8]. However, antimalarial activity of this plant extract has not yet been reported.…”
Section: Introductionmentioning
confidence: 97%